Load Monitoring Using Surface Response to Excitation Method - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
Surface response to excitation (SuRE) method is a low-cost alternative to the electromechanical impedance method developed for the structural health monitoring (SHM) applications. This method uses one piezoelectric transducer to excite the surface of a structure with a sweep sine wave. One or more piezoelectric sensors or scanning laser vibrometer monitors the dynamic response of the surface to the excitation. The spectrum of the dynamic response is collected at the optimal operating conditions. Any significant change of the spectral characteristics may indicate defects, improper loading or loose fasteners. In this study, the performance of SuRE method was evaluated when the conventional piezoelectric elements and scanning laser vibrometer were used for monitoring the presence of loads on the surface. In order to determine the accuracy and reliability of both monitoring approaches two tests were performed. In the first test, one piezoelectric transducer was used as exciter and another one as a sensor. In the second test, a scanning laser vibrometer was used to measure the surface vibrations. Although the piezoelectric element collected the data with better resolution, the results with the scanning laser vibrometer were acceptable and can be used when attaching piezoelectric elements are not allowed to the surface.
Keywords: SHM; Load monitoring; SuRE method; Laser vibrometer; Piezoelectric transducer